2009
DOI: 10.1073/pnas.0810808106
|View full text |Cite
|
Sign up to set email alerts
|

The stability of AID and its function in class-switching are critically sensitive to the identity of its nuclear-export sequence

Abstract: The carboxyterminal region of activation-induced deaminase (AID) is required for its function in Ig class switch recombination (CSR) and also contains a nuclear-export sequence (NES). Here, based on an extensive fine-structure mutation analysis of the AID NES, as well as from AID chimeras bearing heterologous NESs, we show that while a functional NES is indeed essential for CSR, it is not sufficient. The precise nature of the NES is critical both for AID stabilization and CSR function: minor changes in the NES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
90
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 31 publications
7
90
0
Order By: Relevance
“…Microhomology-mediated end-joining also could be the result of impaired recruitment of cofactor(s) involved in the processing/recombination of AID-induced lesions. Several studies have strongly suggested that the C-terminal part of AID could recruit a repair cofactor or target AID to specific areas, such as nuclear pores, thereby providing a special DNA repair/recombination environment (32,33,39). The detection of DSBs in the Sμ region from AID +/C-termΔ B cells supports the impaired recruitment hypothesis for the AID +/C-termΔ group.…”
Section: Position Of Sμ and Sα Breakpoints In Switchsupporting
confidence: 60%
See 1 more Smart Citation
“…Microhomology-mediated end-joining also could be the result of impaired recruitment of cofactor(s) involved in the processing/recombination of AID-induced lesions. Several studies have strongly suggested that the C-terminal part of AID could recruit a repair cofactor or target AID to specific areas, such as nuclear pores, thereby providing a special DNA repair/recombination environment (32,33,39). The detection of DSBs in the Sμ region from AID +/C-termΔ B cells supports the impaired recruitment hypothesis for the AID +/C-termΔ group.…”
Section: Position Of Sμ and Sα Breakpoints In Switchsupporting
confidence: 60%
“…This discrepancy could be related to the sequencing of different regions in Sμ, or to the fact that the murine study analyzed mutations in germline (i.e., unrearranged) Sμ regions from B cells undergoing in vitro CSR, whereas we analyzed rearranged Sμ regions from AID +/C-termΔ patients that were successfully switched in vivo. A recent study suggested that AID participates via its C-terminal part in a multimolecular complex (supposedly at nuclear pores) necessary for its stability and CSR (33). Thus, the lower frequency in the Sμ core region from Sμ-Sα junctions derived from UNG2 −/− and AID +/C-termΔ B cells could be explained by differences in the DNA repair/recombination environment.…”
Section: Position Of Sμ and Sα Breakpoints In Switchmentioning
confidence: 99%
“…To investigate the possible involvement of AID's specific NES in the eEF1A interaction, we asked whether the interaction was retained with a multiply mutated NES mutant (M8) that nevertheless confers nuclear export function and protein stabilization (15). The results reveal that AID's NES can be substantially altered without seriously jeopardizing the eEF1A interaction (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The N-terminal portion of AID therefore appears necessary (either indirectly or directly) for the eEF1A interaction. The interpretation of the result with chimera E is slightly less straightforward because the removal of the C-terminal region of AID [which also contains its nuclear export sequence (NES) as well as residues implicated in AID's cytosolic retention] results in AID destabilization (9,12,15).…”
Section: Resultsmentioning
confidence: 99%
“…It must be noted that expression levels of mouse mutant D189-198 as well as human mutants JP8B and P20 in GFP-sorted BM cells were lower than those of WTs, possibly due to protein instability of these C-terminal mutants. 30 Therefore, we cannot answer the question whether CSR activity is indispensable for oncogenicity of AID, but we assume that the maximum ability of AID to cause lymphoma requires an intact form of AID with SHM activity.…”
Section: Discussionmentioning
confidence: 99%